Il caso peruviano delle sterilizzazioni: la politicizzazione del corpo femminile tra autoritarismo e democrazia (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2020)
The 20th century will be remembered as a time frame in which human rights have been contemporarily promoted and violated more than ever. In particular, a new arena emerged for fights between governments and civil society: the female body. From an intimate and individual matter, motherhood became a political and public issue, where women were leaders and victims at once. Contraception became the mean by which women either claimed their empowerment or suffered male control. The Peruvian case of sterilizations shows how a contraceptive method has been paradoxically used to both promote women’s health and violate their human rights.
Keywords: Sterilization; Fujimori; Feminism; Peru; Family Planning